CREDIT SCORING AND ITS ROLE IN UNDERWRITING - Afgan Imanzade (The International Scientific Association of Economists “CONSILIUM”; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The main goal of the research is to study the opportunities for active utilization of credit scoring in the banking, as well as the financial sectors and methods for mutual ensuring of interests of market participants. The article addresses the indicators, that affect the formation of scoring, its macroeconomic benefits, and investigates the history of scoring and the international practice. The article also analyzes the role, the deployment of scoring may play in minimizing losses likely to occur at the end of the transaction term while measuring credit risks of credit institutions that concentrate available financial resources, as well as insurance companies, another chain of the financial system. At the same time, the article addresses how the introduction of scoring may affect access to low-cost financial resources. The role of scoring in timely implementation of liabilities by borrowers and in easy access to favorable financial resources created by the responsible lending may act as a practical significance of the study.
Keywords: G21; G22; G29; H81; 330; credit scoring; credit underwriting